MAKING A MODEL OF THE CELERY USING STEM TEACHING TECHNOLOGY IN LABORATORY EXERCISES IN ASTRONOMY - Sunnatova O’g’iloy Kamardin qizi; Sayfullayeva G. I. (Web of Journals Publishing, 2023)
STEM this — S – science, T – technology, E – engineering and M – mathematics. When we translate from English into English, this is how it happens: natural sciences, technology, engineering, art and mathematics. We need to realize that these trends are becoming the most popular in the modern world. On this basis, today the STEM education system is developing as one of the main trends.
Keywords: competence, experimentation, STEM, electrical chain, industry, element.